Testing of different quality filtering algorithms on contig quality in plant transcriptome - Kroll, Laura-Nadine (Jihočeská univerzita, 2020)
RNA sequences of the carnivorous plant Utricularia vulgaris were used to test the impor- tance of RNA sequence quality control tools and the influence of those tools on a sequence assembly. Three quality control tools were examined, followed up by the testing of two dif- ferent assemblers. The results were then compared and evaluated.
Testing of different quality filtering algorithms on contig quality in plant transcriptome
Keywords: quality control; RNA-sequences; transcriptome assembly; Utricularia vulgaris; assembly algorithms